Fiji's noni finds a juicy market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The noni fruit (Morinda citrifolia) has been traditionally used in the Caribbean and Pacific as a medicine. Now it has found a new fashionable use, despite its nauseating smell as a fresh fruit. Its juice has found favour with the consumers of the...